Comparison of Scheduling Algorithms in The Design of Fault Tolerant Real Time Systems - Swarna Latha Gade, Mary; Sreenivasa Ravi, K (International Journal of Engineering and Technology, 2018)
Most of the real time systems have the timing constraints. The main important timing constraints of any real time systems are to meet the deadlines of its application tasks. Not only satisfying the timing constraints of any real-time system, but also the functional correctness of application needs to be guaranteed. Meeting the dead line of application is no use if it deviates from its precise output. Timing constraints of the system can be satisfied by choosing proper task scheduling algorithms and the reliability of the system can be reached by providing fault-tolerance. In this paper, various fault scheduling algorithms like fixed priority, EDF(Earliest dead line first), LLF (Least Laxity First),Rate monotonic etc have been studied and compare the parameters like Worst-case execution times, response time, task missed deadlines, Number of preemption, number of context switches, DeadlockÂ and processor utilization factor.Â